Revision of Halosydna Kinberg, 1856 (Annelida: Polychaeta: Polynoidae) from the Tropical Eastern Pacific and Grand Caribbean with descriptions of new species - Salazar-Silva, P. (Journal of Natural History, 2013)
The genus Halosydna is a member of the family Polynoidae, comprising a group of polychaete annelids commonly known as scale worms. The main results in this study are the redescriptions of 14 species. Four new species are described from the Mexican Pacific. Halosydna leucohyba is newly recorded for the Mexican Caribbean, and H. leius and H. tuberculifer from the Mexican Pacific. The identities of some widely recorded species are clarified, among them H. brevisetosa, H. glabra, H. fuscomarmorata and H. parva. Finally, H. nebulosa and H. virgini are re-established as valid species and a dichotomous key for Halosydna specimens from the tropical eastern Pacific, Grand Caribbean, and other worldwide localities is included
World Polychaeta Database (WPolyDb)